Inhibiting factors of metaverse adoption in Indonesian education: A literature review - Nadia Rewara; Nida Aulia Faridah; Tegar Tasa Wijay (Himpunan Pengembang Kurikulum Indonesia, 2024)
Science is always evolving, and education and technology are no exception. As science develops, education and technology become an integrated whole. In the era of technological development 5.0, a new term has now been recognized, namely 'metaverse'. Metaverse is a technology that can eliminate the boundaries of space and time so that a person can feel the presence of a virtual world directly. It is inevitable that this metaverse technology also penetrates into the realm of education. This research aims to examine the issues in the form of challenges from the metaverse that are being faced by the realm of education in Indonesia. This research is useful for educational actors in Indonesia to understand the urgency in answering the challenges of this metaverse technology. The research method used is the Systematic Literature Review (SLR) method where as much information as possible is collected and then interpreted in depth. The findings of this research are in the form of various challenges to the issue of metaverse in education to then be a motivation for readers in finding solutions to the integration of metaverse in the realm of education itself. Abstrak Ilmu pengetahuan selalu mengalami perkembangan, tak terkecuali di bidang pendidikan dan teknologi. Seiring berkembangnya keilmuan, pendidikan dan teknologi menjadi suatu kesatuan yang saling terintegrasi. Pada era perkembangan teknologi 5.0 kini telah dikenal istilah baru yakni ‘metaverse’. Penelitian ini bertujuan untuk mengkaji isu berupa tantangan dari metaverse yang tengah dihadapi ranah pendidikan di Indonesia. Penelitian ini bermanfaat bagi para pelaku pendidikan di Indonesia untuk memahami urgensi dalam menjawab tantangan dari teknologi metaverse ini. Metode penelitian yang digunakan adalah metode Systematic Literature Review (SLR) dimana dilakukan pengumpulan informasi sebanyak-banyaknya untuk kemudian ditafsirkan secara mendalam. Temuan dari penelitian ini adalah terdapat tantangan-tantangan teknis seperti ketersediaan infrastruktur, keberlanjutan penggunaan teknologi, dukungan institusi, kesiapan guru dan peserta didik, serta peran komunitas yang menghambat integrasi metaverse dalam proses pembelajaran. Adapun faktor-faktor kunci yang perlu diperhatikan untuk menerapkan Metaverse dalam pendidikan mencakup psychological and motivational, quality, social, dan inhibiting factors. Temuan ini dapat menjadi motivasi bagi pembaca dalam menemukan solusi atas integrasi metaverse dalam ranah pendidikan itu sendiri. Kata Kunci: faktor penghambat; metaverse; pendidikan